MARKETING STRATEGY THROUGH INSTAGRAM SOCIAL MEDIA: (Study at Nazwa Hijab Kendari Clothing Store) - Wahyudin Maguni; Abdul Wahid Mongkito; Sumiyadi Sumiyadi; La Hadisi; Dwi Resti Akhiria (Faculty of Science and Technology University of Pramita Indonesia, 2023)
This research is motivated by the lack of knowledge of a company in utilizing Instagram Social Media as a tool to market its business. Usually, business actors do not really understand how to run a company well, this is one of the factors why marketing strategies are very important in running a business. This study aims to find out how the Marketing Strategy Through Instagram Social Media at Nazwa Hijab Kendari Shop. This study uses a type of research with a qualitative approach, using the Snowball Ball sampling technique. The objects in this study are the Owners of Nazwa Hijab Kendari, consumers, and employees regarding the marketing strategy at the Nazwa Hijab Kendari Store. The research instrument uses three indicators, namely interview guidelines, observation guidelines and documentation guidelines. The results of this study prove that partially Nazwa Hijab Kendari Store uses a marketing strategy in running a company using Instagram social media. The marketing strategy carried out is in the form of segmentation, targeting and positioning strategies in market segmentation. The Nazwa Hijab shop also uses a sharia marketing strategy by following the example of marketing carried out during the time of the Prophet Muhammad.